Stress-responsive FKBP51 regulates AKT2-AS160 signaling and metabolic function - Georgia Balsevich (Nature Portfolio, 2017)
Stress is recognized as risk factor for the development of type 2 diabetes. Here Balsevich et al. show that the stress responsive co-chaperone FKBP5 regulates glucose metabolism in mice by modulating AS160 phosphorylation, glucose transporter expression and muscle glucose uptake.